Polyphenols as a new class of prebiotics for gut microbiota manipulation - Bačić, Ana; Gavrilović, Jelisaveta; Rajilić-Stojanović, Mirjana (Archives of Pharmacy, 2023)
A thriving community of microorganisms resides in our intestines, forming complex interactions and producing signaling molecules that can affect human physiological processes. Intrinsic and environmental factors modulate the composition of the microbial ecosystem, with diet representing a key factor affecting the formation of gut microbiota. The epidemic of non-communicable chronic diseases has been associated with the Western diet, which may modulate the gut microbiota, resulting in a detrimental derangement in the microbial community, termed dysbiosis. Dysbiosis may be reverted through dietary interventions and the application of probiotics and prebiotics. Phenolic compounds represent plant-based nutraceuticals, which can be separated into phenolic acids and polyphenols, that exert prebiotic-like effects and may prevent the development of diseases. Besides direct health-promoting activities, beneficial effects of phenolic compounds may be exerted through their interaction with the gut microbiota. A bidirectional relationship between the gut microbiota and phenolic compounds has been observed, as microorganisms are involved in the metabolism of phenolic compounds, whereas phenolic compounds may affect the composition of the microbiota, with selective stimulatory or inhibitory activity towards the growth of microbial members. In this review, insight into the gut microbiota-polyphenols relationship will be given, with a focus on the application of polyphenols for modifying microbiota and promoting health.
Keywords: polyphenols; microbiota; prebiotic; quorum-sensing